2023
DOI: 10.1021/acs.chemrev.3c00146
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Surfactant: A Mighty Thin Film

Fred Possmayer,
Yi Y. Zuo,
Ruud A. W. Veldhuizen
et al.

Abstract: Pulmonary surfactant is a critical component of lung function in healthy individuals. It functions in part by lowering surface tension in the alveoli, thereby allowing for breathing with minimal effort. The prevailing thinking is that low surface tension is attained by a compression-driven squeeze-out of unsaturated phospholipids during exhalation, forming a film enriched in saturated phospholipids that achieves surface tensions close to zero. A thorough review of past and recent literature suggests that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 726 publications
(2,193 reference statements)
0
3
0
Order By: Relevance
“…It was found that the addition of MPs/NPs significantly decreases the vesicle size of Infasurf (Figure S4). This indicates denaturation of surfactant-associated proteins (SP-B/C), since these small, hydrophobic proteins promote the formation of large vesicular aggregates by inducing membrane fusion. , Decreasing phospholipid vesicle size in natural pulmonary surfactants is a strong indication of surfactant inhibition. , Figure depicts the main findings and the EHS impact of this study.…”
Section: Discussionmentioning
confidence: 72%
“…It was found that the addition of MPs/NPs significantly decreases the vesicle size of Infasurf (Figure S4). This indicates denaturation of surfactant-associated proteins (SP-B/C), since these small, hydrophobic proteins promote the formation of large vesicular aggregates by inducing membrane fusion. , Decreasing phospholipid vesicle size in natural pulmonary surfactants is a strong indication of surfactant inhibition. , Figure depicts the main findings and the EHS impact of this study.…”
Section: Discussionmentioning
confidence: 72%
“…We have previously suggested that the biological target of poisonings by the inhalation of waterproofing products is the lung surfactant in the respiratory parts of the lungs [11]. Lung surfactant is secreted into the thin liquid lining covering the respiratory parts of the lungs, where it regulates surface tension at the air-liquid interface in the alveoli [12,13]. The regulation of surface tension during breathing is essential for normal lung function, and the disruption of lung surfactant function can lead to decreased lung function, as described in an adverse outcome pathway [14] and https://aopwiki.org/aops/302 (accessed on 1 March 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Lung surfactant is a mixture of lipids and proteins synthesized by alveolar type 2 cells and secreted into the lung alveoli where it reduces surface tension at the air-liquid interface [1,2]. Mammalian lung surfactant contains about 80% phospholipids, 10% neutral lipids, and 10% protein.…”
Section: Introductionmentioning
confidence: 99%